Therapeutic potential of procathepsin L-inhibiting and progesterone-entrapping dimethyl-β-cyclodextrin nanoparticles in treating experimental sepsis - Qiang, Xiaoling; Chen, Weiqiang; Zhu, Cassie Shu; Li, Jianhua; Qi, Timothy; Lou, Li; Wang, Ping; Tracey, Kevin J.; Wang, Haichao (Frontiers in Immunology, 2024)
The pathogenic mechanisms of bacterial infections and resultant sepsis are partly attributed to dysregulated inflammatory responses sustained by some late-acting mediators including the procathepsin-L (pCTS-L). It was entirely unknown whether any compounds of the U.S. Drug Collection could suppress pCTS-L-induced inflammation, and pharmacologically be exploited into possible therapies. Here, we demonstrated that a macrophage cell-based screening of a U.S. Drug Collection of 1360 compounds resulted in the identification of progesterone (PRO) as an inhibitor of pCTS-L-mediated production of several chemokines [e.g., Epithelial Neutrophil-Activating Peptide (ENA-78), Monocyte Chemoattractant Protein-1 (MCP-1) or MCP-3] and cytokines [e.g., Interleukin-10 (IL-10) or Tumor Necrosis Factor (TNF)] in primary human peripheral blood mononuclear cells (PBMCs). In vivo, these PRO-entrapping 2,6-dimethal-βcyclodextrin (DM-β-CD) nanoparticles (containing 1.35 mg/kg PRO and 14.65 mg/kg DM-β-CD) significantly increased animal survival in both male (from 30% to 70%, n = 20, P = 0.041) and female (from 50% to 80%, n = 30, P = 0.026) mice even when they were initially administered at 24 h post the onset of sepsis. This protective effect was associated with a reduction of sepsistriggered accumulation of three surrogate biomarkers [e.g., Granulocyte Colony Stimulating Factor (G-CSF) by 40%; Macrophage Inflammatory Protein-2 (MIP-2) by 45%; and Soluble Tumor Necrosis Factor Receptor I (sTNFRI) by 80%]. Surface Plasmon Resonance (SPR) analysis revealed a strong interaction between PRO and pCTS-L (KD = 78.2 ± 33.7 nM), which was paralleled with a positive correlation between serum PRO concentration and serum pCTS-L level ( = 0.56, P = 0.0009) or disease severity (Sequential Organ Failure Assessment, SOFA;  = 0.64, P = 0.0001) score in septic patients. Our observations support a promising opportunity to explore DM-β-CD nanoparticles entrapping lipophilic drugs as possible therapies for clinical sepsis.